The Effect of Mothers' Voice on Preterm Neonates' Physiological Parameters - Fatemeh Cheraghi; Zahra Afshari; Leili Tapak; Tahereh Sabouri; Efat Sadeghian (Hamadan University of Medical Sciences, 2017)
Introduction: Favorable auditory stimulation improves the preterm neonates' physiological function. Thus this study investigates the effect of mothers' Voice on preterm  neonates' physiological  parameters.   Methods: This one group, pre-post-test clinical trial was conducted in NICU of Mehr Hospital in Malayer, 2016. Thirty-six preterm neonates with gestational age (32-37 weeks) and birth aged 3-28 days were selected by simple random sampling. The mother of each neonate talked with her own baby for ten minutes in three days whispering. Arterial blood oxygen saturation (SpO2), heart rate (HR) and respiratory rate (RR) were measured three times, 5 minutes before, 10 minutes within and 5 minutes after intervention each day. Data was analyzed using SPSS22 and descriptive statistics such as mean, standard deviation and analysis of variance with repeated measures and Tukey multiple comparison tests. Confidence level was 0.95. Results: The mean SpO2, RR and HR values were significantly difference between three times of measurement in each day (P<0.001). According to Tukey test, the mean SpO2 values increased and Mean RR and HR values decreased between three times of measurement in each day. Conclusion: The live whisper of own mother improves the physiological parameters of the preterm neonate. SpO2 increased, HR and RR decreased. Therefore, in daily nursing care planning, the nurses can give the mothers time to talk to their babies.